2008
DOI: 10.1105/tpc.108.058180
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effects of miR156-TargetedSPLGenes andCYP78A5/KLUHon Plastochron Length and Organ Size inArabidopsis thaliana   

Abstract: Leaves of flowering plants are produced from the shoot apical meristem at regular intervals, with the time that elapses between the formation of two successive leaf primordia defining the plastochron. We have identified two genetic axes affecting plastochron length in Arabidopsis thaliana. One involves microRNA156 (miR156), which targets a series of SQUAMOSA PROMOTER BINDING PROTEIN-LIKE (SPL) genes. In situ hybridization studies and misexpression experiments demonstrate that miR156 is a quantitative, rather t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
455
3
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 471 publications
(503 citation statements)
references
References 91 publications
25
455
3
5
Order By: Relevance
“…The cytokinin mutants and transgenic plants mentioned above have much smaller SAM and fewer leaves compared with the wild type, which is indicative of a longer plastochron (Werner et al, 2001(Werner et al, , 2003Higuchi et al, 2004;Nishimura et al, 2004;Miyawaki et al, 2006). Upregulation of SQUAMOSA PROMOTER BINDING PROTEIN-LIKE9 expression results in both a smaller size of the meristem and a longer plastochron (Wang et al, 2008). On the other hand, bigger SAM size of clavata1 and altered meristem program1 mutants was accompanied by shorter plastochron length (Chaudhury et al, 1993;Kwon et al, 2005;Vidaurre et al, 2007).…”
Section: Mechanisms By Which Gif Genes Regulate Cell Proliferation Dumentioning
confidence: 99%
“…The cytokinin mutants and transgenic plants mentioned above have much smaller SAM and fewer leaves compared with the wild type, which is indicative of a longer plastochron (Werner et al, 2001(Werner et al, , 2003Higuchi et al, 2004;Nishimura et al, 2004;Miyawaki et al, 2006). Upregulation of SQUAMOSA PROMOTER BINDING PROTEIN-LIKE9 expression results in both a smaller size of the meristem and a longer plastochron (Wang et al, 2008). On the other hand, bigger SAM size of clavata1 and altered meristem program1 mutants was accompanied by shorter plastochron length (Chaudhury et al, 1993;Kwon et al, 2005;Vidaurre et al, 2007).…”
Section: Mechanisms By Which Gif Genes Regulate Cell Proliferation Dumentioning
confidence: 99%
“…spl2-1, spl9-4, and spl15-1 have either no (spl2-1) or a very small (spl9-4 and spl15-1) effect on shoot development as single mutations but produce a significant delay in abaxial trichome production and an increase in the rate of leaf production in multiple mutant combinations (22,23) (Fig. 2 C, G, and H).…”
Section: The Precocious Phenotype Of Sqn Is a Consequence Of The Elevmentioning
confidence: 99%
“…Previous studies in both Arabidopsis and maize have shown that constitutive expression of the microRNA (miRNA) miR156 prolongs the expression of the juvenile phase of vegetative development and increases the rate of leaf initiation (19)(20)(21)(22)(23). In Arabidopsis, miR156 regulates 10 members of the SPL family of transcription factors (24).…”
mentioning
confidence: 99%
“…This shared phenotype between the different genes indicates that they might act on a related metabolic network (Zondlo and Irish, 1999;Ito and Meyerowitz, 2000;Marsch-Martinez et al, 2002;Fang et al, 2012). An insertional knockout line for KLUH/ CYP78A5 showed a higher rate of leaf initiation (Wang et al, 2008). The smaller size of leaves, sepals, and petals in homozygous cyp78a5/klu plants was found to be due to a decreased cell number and not caused by a decreased cell size (Anastasiou et al, 2007).…”
mentioning
confidence: 99%
“…KLUH/CYP78A5 is expressed in the inner integument of developing ovules and stimulates cell proliferation, thereby determining seed size (Adamski et al, 2009). A loss-of-function mutant for the closely related gene CYP78A7 has also been isolated, although it does not show an evident phenotype (Wang et al, 2008). However, embryos of the double knockout mutant cyp78a5/ klu cyp78a7 did not develop correctly.…”
mentioning
confidence: 99%